MEDIA BALOK UNTUK KEMAMPUAN KOGNITIF ANAK USIA DINI DI KELOMPOK A RA SUNAN GIRI SUMBERJAYA GONDANGLEGI-MALANG - Wika Mala, Nilna Farhata; Permata Sari, Ratih (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
The education is an important thing for every individual, especially early childhood, in this case children need good stimulation, one of which is in the cognitive aspect. The purpose of this study was to emphasize the application of block media and the effectiveness of using block media for cognitive development of early childhood in group A RA Sunan Giri Sumberjaya. This study used a descriptive-qualitative research method with the research subjects being group A children, totaling 28 children. Data collection techniques used are observation, interviews and documentation. Data were analyzed using data reduction, data presentation and drawing conclusions. The results and discussion emphasize the development of educator competencies in implementing activities to recognize the concept of numbers, understand shapes and train children's creativity. Meanwhile, the effectiveness of the block media can be known through memory in solving problems during the learning process of the concept of number, shape, size and color. The research can be concluded that the learning that is carried out by improving the quality of the media, the competence of teachers in innovating in their work can be improved.